2018
DOI: 10.1186/s10194-018-0936-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive vagus nerve stimulation for treatment of cluster headache: early UK clinical experience

Abstract: BackgroundEvidence supports the use of non-invasive vagus nerve stimulation (nVNS; gammaCore®) as a promising therapeutic option for patients with cluster headache (CH). We conducted this audit of real-world data from patients with CH, the majority of whom were treatment refractory, to explore early UK clinical experience with nVNS used acutely, preventively, or both.MethodsWe retrospectively analysed data from 30 patients with CH (29 chronic, 1 episodic) who submitted individual funding requests for nVNS to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…In a previous open-label pilot study of 20 patients with migraine who received preventive and acute nVNS therapy for 3 months, the reduction in headache days per month was −5.8 days (15), which compares favourably with the headache day reduction in this study (−2.7 days) in which patients received preventive nVNS only. These clinical data are consistent with the mechanistic evidence supporting the potential synergy of acute and preventive nVNS treatment in migraine (15,2224,34). The ability of nVNS to provide acute and preventive benefits would represent a novel clinical option, as pharmacologic migraine therapies are indicated only as either preventive or acute treatment.…”
Section: Discussionsupporting
confidence: 87%
“…In a previous open-label pilot study of 20 patients with migraine who received preventive and acute nVNS therapy for 3 months, the reduction in headache days per month was −5.8 days (15), which compares favourably with the headache day reduction in this study (−2.7 days) in which patients received preventive nVNS only. These clinical data are consistent with the mechanistic evidence supporting the potential synergy of acute and preventive nVNS treatment in migraine (15,2224,34). The ability of nVNS to provide acute and preventive benefits would represent a novel clinical option, as pharmacologic migraine therapies are indicated only as either preventive or acute treatment.…”
Section: Discussionsupporting
confidence: 87%
“…No differences in the efficacy of nVNS as acute or preventive therapy were apparent between eCH and cCH subtypes, although not all treatment outcomes were formally compared between the CH subtypes. Benefits of individually adjusted dosing in patients with cCH are also supported by findings from a retrospective review of nVNS in patients with treatment-refractory CH ( 34 ). Such results are from open-label studies, but are nevertheless pertinent given that sustained improvements were noted in several patients with CH that had been refractory to treatment.…”
Section: Discussionmentioning
confidence: 79%
“…The PREVA24 study indicated a significantly greater reduction in the number of attacks per week versus controls (−5.9 vs −2.1, respectively) for a mean therapeutic gain of 3.9 fewer attacks per week (p=0.02). Marin et al ’s25 study demonstrated a decrease in mean attack frequency from 26.6 attacks per week before initiation of nVNS treatment to 9.5 attacks per week (p<0.01) afterward.…”
Section: Discussionmentioning
confidence: 92%